Istilah : kerajaan, perundangan dan perdagangan - Arba'ie Sujud; Anandan Krishnan; Hashim Musa; Hasnah Mohamad; Raja Masitah Raja Ariffin (Sweet & Maxwell Asia, 2013)
English and Malay glossary of terms and phrases commonly used in the legal, governmental, and commercial contexts